2018
DOI: 10.1175/jamc-d-18-0146.1
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Extreme South American Andean Cold Surges

Abstract: Cold surges represent one of several phenomena by which midlatitude features can modulate the atmosphere, both dynamically and thermodynamically, deep into the tropics. This study involves the construction of a climatology of the strongest South American cold surges that follow along the Andes Mountains to quantify the extent to which these surges modulate the atmosphere from the midlatitudes to the tropics. Cold surges occurring during June–September (austral winter) from 1980 to 2017 are considered. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Therefore, the arrival of the friagem phenomenon in the Amazon region is characterized by the change in the wind direction in the southwest and central regions of the Amazon and by abrupt drops in the values of temperature, especially in the southwest. Similar results were also found by other authors (Fisch, 1996;Marengo et al, 1997;Fisch et al, 1998;de Oliveira et al, 2004;Ricarte et al, 2015;Viana and Herdies, 2018).…”
Section: Environmental Characteristics In the Amazon Basin Scalesupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the arrival of the friagem phenomenon in the Amazon region is characterized by the change in the wind direction in the southwest and central regions of the Amazon and by abrupt drops in the values of temperature, especially in the southwest. Similar results were also found by other authors (Fisch, 1996;Marengo et al, 1997;Fisch et al, 1998;de Oliveira et al, 2004;Ricarte et al, 2015;Viana and Herdies, 2018).…”
Section: Environmental Characteristics In the Amazon Basin Scalesupporting
confidence: 92%
“…The Amazon region suffers from the incursion of cold waves from the high latitudes of the Southern Hemisphere (SH), with a relatively common occurrence mainly in the less rainy season, between June and September. These events are de-nominated locally and in literature as friagem, and about 70 % of the cases of friagem occur in this period of the year (Brinkmann and Ribeiro, 1972;Marengo et al, 1997;Fisch et al, 1998;de Oliveira et al, 2004;Caraballo et al, 2014;Ricarte et al, 2015;Viana and Herdies, 2018). Brinkmann and Ribeiro (1972) observed two to three friagem events per year, predominantly in the less rainy season, in the central Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the reviewer's comments. We will respond in parts: (1): The reasons for choosing the case study shown in the manuscript (July 6 to 11, 2014), were as follows: i) July is one of the months with the largest number of cold fronts that arrive in the South-Southeastern region of Brazil (Prince and Evans, 2018). Consequently, July is also the month where a greater number of Friagem phenomena are observed in the Amazon region (Prince and Evans, 2018).…”
Section: Answermentioning
confidence: 99%
“…We will respond in parts: (1): The reasons for choosing the case study shown in the manuscript (July 6 to 11, 2014), were as follows: i) July is one of the months with the largest number of cold fronts that arrive in the South-Southeastern region of Brazil (Prince and Evans, 2018). Consequently, July is also the month where a greater number of Friagem phenomena are observed in the Amazon region (Prince and Evans, 2018). ii) Throughout 2014, intensive activities of the GoAmazon project took place (Martin et al, 2016), that is, measurements of gases and the thermodynamics of the atmosphere were carried out in several sites investigated in this work (T2, T3 and T0z), and therefore this was the motivation for choosing the year 2014 for our case study.…”
Section: Answermentioning
confidence: 99%
“…Boers et al (2014) showed that more than 60% of these extreme events are associated with preceding extreme rainfall (within 2 days) in the region of South-East South America (SESA) and a low pressure anomaly in north-western (NW) Argentina. These authors associated the northward migration of a frontal system with cold surges, one of the major climate features affecting South American rainfall patterns, particularly during the wet season (e.g., Marengo et al 1997;Garreaud and Wallace 1998;Garreaud 2000;Lupo et al 2001;Vera and Vigliarolo 2002;Espinoza et al 2012;Rasmussen and Houze 2016;Sicart et al 2016;Paccini et al 2018;Prince and Evans 2018). While their study identifies the spatiotemporal correlation between rainfall events in SESA and the eastern Central Andes, they do not analyze the atmospheric dynamics leading to these events.…”
Section: Introductionmentioning
confidence: 99%